Safe Houses as Instruments of Witness and Victim Protection: Effectiveness and Implementation Challenges - Akbar, Okky Iman (Soedirman Law Review, 2025)
Witness and victim protection constitutes a fundamental pillar of a fair and effective criminal justice system, particularly in contexts where intimidation, retaliation, and psychological pressure threaten the integrity of legal proceedings. In Indonesia, the Witness and Victim Protection Agency (Lembaga Perlindungan Saksi dan Korban - LPSK) implements safe houses as a form of physical and non-physical protection, yet questions remain regarding their practical effectiveness and sustainability. This study aims to examine the effectiveness of safe houses in protecting witnesses and victims and to identify the principal challenges faced by LPSK in implementing this protection mechanism. The research adopts a socio-legal methodology with an empirical juridical approach, combining qualitative interviews, indirect observation, and document analysis of relevant legislation and institutional reports. The findings demonstrate that LPSK safe houses are generally effective in fulfilling their protective objectives, particularly through strict security standards, confidentiality, legal assistance, and psychological and psychosocial support. However, the study also reveals significant implementation challenges, especially related to institutional workload, budget constraints, and cultural tensions arising from restrictive security measures such as limitations on personal communication devices. These restrictions, while legally justified, often negatively affect the psychological well-being and compliance of protected individuals and in some cases lead to early termination of protection. In conclusion, safe houses remain a vital instrument in witness and victim protection in Indonesia, but their effectiveness depends on balancing security imperatives with psychosocial needs. This study recommends adaptive protection policies and more innovative institutional strategies to enhance long-term effectiveness without compromising security.Keywords: Effectiveness; Safe Houses; Witness and Victim Protection.